(untitled) (Herald of Journalism, 2020)
This scientific article describes that the language of the media has a powerful stimulating effect on the development of modern language situa- tion. The rapid development of the society, rapid advances in science and technology caused the need for the formation of a special language, well fitted for the expression and transmission of scientific language, where it exhibits unique skills of journalists. However, in this article we detailed the following main functions and tasks of journalism, as communication and information functions and impacts; explain the principle of the first func- tion – the message fresh and timely news and implementation through any periodicals and distribution channels as soon as possible, as well, shows the functions of their impact – this conviction with the help of facts, evi- dence system, images, etc.